Pengaruh Terapi Foot Massage terhadap Penurunan Tingkat Keletihan pada Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisa - Tyas Abdi Pangesti; Resti Yulianti Sutrisno; Purnomo Widiyanto (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Patients who experience Chronic Kidney Failure (CKD) require hemodialysis therapy. Fatigue is one of the effects of CKD and hemodialysis therapy. Fatigue occurs due to prolonged hemodialysis, anemia, uremic syndrome, and decreased blood pressure due to the effects of hemodialysis. One of the non-pharmacological therapies that can reduce fatigue in hemodialysis patients is foot massage therapy. This case study aims to determine the reduction in fatigue levels after carrying out foot massage therapy in CKD patients undergoing hemodialysis. This research design uses a case study to evaluate the implementation of nursing through foot massage therapy. The measuring tool used is the Functional Assessment Chronic Illness Therapy (FACIT) Fatigue Scale. This intervention was given at the 1st, 2nd, and 3rd hours for 10 minutes (starting at 51-60 minutes) for 3 days in the hospital hemodialysis unit and at home for 4 days for a total of 7 days. Evaluation of respondents' level of fatigue was carried out on days 1, 5, and 8. The results of this study showed that the fatigue level score after the intervention from days 1 to 7 decreased. The fatigue level score on day 1 was 15 (severe category), the score on day 5 was 21.66 (moderate category), and day 8 was 24.55 (moderate category). It can be concluded that foot massage therapy can reduce fatigue in CKD patients undergoing hemodialysis. The results of this research can be applied independently by nurses for CKD patients undergoing hemodialysis to reduce fatigue levels.